Some surface characterıstıcs of orıental beech wood ımpregnated wıth some fıre-retardants and coated wıth polyurea/polyurethane hybrıd and epoxy resıns - Altay, Çağlar; Toker, Hilmi; Baysal, Ergün; Babahan, İlknur (Maderas. Ciencia y Tecnología, 2021)
This study was made to determine surface characteristics such as colour, gloss, and surface hardness changes of Oriental beech (Fagus orientalis). The wood specimens were firstly impregnated with some fire-retardants (FRs) and primed with epoxy resin (EPR) and then coated with polyurethane/polyurea hybrid resin (PUU). Oriental beech was impregnated with 3 % aqueous solution of boric acid (BA), borax (BX), boric acid and borax mixture (1:1), and ammonium sulphate (AS). While Sikafloor®-156 was used for epoxy coating (EPR), Sikalastic®-851 R was used for polyurethane/polyurea hybrid coating (PUU). According to our results, all treatment groups gave negative lightness stability values after accelerated weathering. The colour stability of epoxy resin coated Oriental beech was higher than that of polyurethane/polyurea hybrid resin coated Oriental beech. Except for boric acid impregnated and polyurethane/polyurea hybrid resin coated Oriental beech, all fire-retardants treatment before polyurethane/polyurea hybrid resin and epoxy resin coatings decreased the gloss losses of Oriental beech after accelerated weathering. Fire-retardants impregnation before epoxy resin and polyurethane/polyurea hybrid resin coatings improved the surface hardness values of Oriental beech after accelerated weathering.